2008
DOI: 10.1016/j.jconrel.2008.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of a geldanamycin prodrug in mPEG-b-PCL micelles greatly enhances tolerability and pharmacokinetics in rats

Abstract: Geldanamycin (GA) and its analogues inhibit heat shock protein 90 (Hsp90) and have shown significant antitumor activity in vivo; however, clinical development of GA has been hampered by its poor solubility and severe hepatotoxicity. More soluble analogues, such as 17-DMAG and 17-AAG, are easier to formulate, and have progressed through early clinical trials. However the large volume of distribution and systemic toxicity associated with these analogues may limit their distribution into tumors, thereby severely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…The day before the pharmacokinetic experiment, the right jugular veins of the rats were catheterized with sterile silastic cannula (Dow Corning, Midland, MI, USA) under isoflurane anesthesia via procedures previously published. 28 This involved exposure of the vessel prior to cannula insertion. After cannulation, Intramedic PE-50 polyethylene tubing (Becton, Dickinson and Company, Franklin Lakes, NJ, USA) connected to the cannula was exteriorized through the dorsal skin.…”
Section: Methodsmentioning
confidence: 99%
“…The day before the pharmacokinetic experiment, the right jugular veins of the rats were catheterized with sterile silastic cannula (Dow Corning, Midland, MI, USA) under isoflurane anesthesia via procedures previously published. 28 This involved exposure of the vessel prior to cannula insertion. After cannulation, Intramedic PE-50 polyethylene tubing (Becton, Dickinson and Company, Franklin Lakes, NJ, USA) connected to the cannula was exteriorized through the dorsal skin.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from increasing the release time and effect, this approach may lead to an increase in tolerability of the drugs among drug recipients. Another study by Xiong et al showed an increase in tolerability towards geldanamycin prodrug in rats when formulated in methoxy PEG-b-PCL (5000:9200) micelles [10]. Free prodrug was administered to Sprague Dawley rats at 10, 20 and 40 mg/kg doses and prodrug encapsulated in micelles was administered at 10, 20, 40, and 200 mg/kg doses.…”
Section: Approaches To Sustain Drug Delivery From Micellesmentioning
confidence: 99%
“…Directed changes in the drug molecular structure aimed at forming bioreversible precursors (prodrugs) with increased affinity for the carrier have been explored as a means of preventing premature drug dissociation [1114]. However, the effective use of the prodrug approach poses an additional set of challenges, because the kinetics of prodrug release and subsequent parent compound activation need to be tightly coordinated with that of the NP biodistribution.…”
Section: Introductionmentioning
confidence: 99%